Informatization in Ukraine: Realities, Problems, Prospects - Danyliuk, Mariia; Dmytryshyn, Marta; Goran, Tetyana (European Journal of Sustainable Development, 2021)
Modern sustainable development depends on innovative technologies, complete and adequate information at the right time and place. Ukraine did not stay apart from the world plan to reach sustainable goals until 2030. The global coronavirus pandemic has made adjustments in the development of societies and nations as work, study, and even social contacts have gone online. In this matter, informatization will be on the agenda around the world until it entirely and irreversibly changes it. Due to this, the paper examines the current realities of informatization in Ukraine regarding the pace of information and communication services dissemination, coverage of households with Internet access, and salaries in the industry. Regional measurement of information and communication services is presented. The place of Ukraine in the rating of the Network Readiness Index in 2019-2020 also is analyzed, the strengths and weaknesses of our state in modern informatization are revealed. Based on the conducted research, the distribution of information and communication services in Ukrainian regions and the state as a whole are forecasted; the factors of direct and indirect influence of informatization on the society, economy, and the state are formulated.